Analisis Faktor Faktor Perilaku Indispliner Guru di Lingkungan UPTD SMP Negeri 1 Gunungsitoli Idanoi - Nirwan Serlin Putri Farasi; Eliagus Telaumbanua; Syah Abadi Mendrofa; Maria Magdalena Bate'e (Jurnal Publikasi Manajemen Informatika, 2024)
Indisciplinary behavior is behavior that deviates from established rules or problems that can reduce the quality of learning and generally reduce the quality of school. The reality is that disciplinary behavior leads to negative actions. Therefore, this behavior must be overcome so that it does not become a habit that gets worse over time. This type of research is qualitative research. The data collection technique in this research is interview, observation and documentation methods to answer three of the research objectives. The research found that in terms of factors of disciplinary behavior, namely personality factors and environmental factors, in terms of the impact of disciplinary behavior, the researchers found a negative impact on the learning process and generally reducing the quality of the school, in terms of countermeasures or things to avoid disciplinary behavior, namely the school principal being an example to his subordinates. , emphasize that there are school rules to be obeyed, not to be violated, then remind and personally summon teachers who carry out disciplinary actions, carry out direct supervision or monitoring, carry out training and development.